2002
DOI: 10.1097/00005392-200211000-00046
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Characteristics And Health Related Quality of Life in Men Attending Prostate Cancer Support Groups

Abstract: Men enrolled in support groups have unique sociodemographic characteristics. Their health related quality of life appears to be better than that of other men with prostate cancer. Whether this is related to support group participation is not known. Additional studies are required to determine whether routine support group participation improves outcomes in men with prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 15 publications
5
23
1
1
Order By: Relevance
“…Previous studies in the UK [14,15,18] indicated that participants of support groups are typically female, white, with high education and socioeconomic status. Research from other countries such as the USA [12,13,32], Canada [10] and Australia [33] have produced similar findings.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Previous studies in the UK [14,15,18] indicated that participants of support groups are typically female, white, with high education and socioeconomic status. Research from other countries such as the USA [12,13,32], Canada [10] and Australia [33] have produced similar findings.…”
Section: Discussionmentioning
confidence: 55%
“…There were tendencies for more participants than non-participants to be female, younger and further away from diagnosis and have higher educational attainment and socioeconomic status. Existing social support or degree of distress did not reliably predict attendance at groups [8,10,12].…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Since the 1990s, many prostate cancer support groups (PCSGs) have formed to offer men information and education, assistance with decision making, and peer-networking (Coreil and Ravish, 1999;Gray et al, 1996Gray et al, , 1997Gray et al, , 2000aManne, 2002;Prostate Cancer Canada Network, 2010;Steginga et al, 2001). There is evidence that PCSGs are especially useful in mitigating the psychosocial aspects of cancer by conveying information, empowering patients, enhancing and facilitating men's adjustment, and helping patients cope with life after a diagnosis and treatment of cancer (Cordova et al, 2003;Evans and Connis, 1995;Fawzy et al, 1990;Katz et al, 2002;Manne, 2002;Sharp and Aviv, 1996;Spiegel et al, 1981;Steginga et al, 2001). However, the specificities of what underpins such benefits are poorly understood, and we decided to formally examine attendees' interactions and practices around health literacy and consumerism.…”
Section: Introductionmentioning
confidence: 99%